Smoking and vaping trends among active-duty U.S. Navy and Marine Corps personnel: results from the Annual Periodic Health Assessment, 2017-2021 - James K Romine; Amber L Dougherty; Eyal Oren; Giovanni Appolon; Andrew J MacGregor (Nicotine & Tobacco Research, 2026)
Abstract Introduction This study compared annual prevalences of traditional cigarette smoking versus e-cigarette vaping among active-duty U.S. Navy or Marine Corps personnel from 2017 to 2021. Methods Trends were estimated using the annual Periodic Health Assessment (PHA), a standardized evaluation of medical readiness for military duties. We estimated crude and age-adjusted prevalences of tobacco-use type for each annual PHA and plotted linear trends. Results The study included 496,079 active-duty service members who completed ≥1 PHA between 2017 and 2021. Trends of cigarette smoking were inversely related to e-cigarette vaping; as smoking decreased, vaping increased. The age-adjusted annual prevalence of cigarette smoking (single-product use) declined from 7.7% to 4.2%. In contrast, the age-adjusted annual prevalence of e-cigarette vaping increased from 2.8% to 8.3%. Conclusions By the end of the study period, single-product use of e-cigarettes (vaping) was nearly twice as prevalent as cigarette smoking—a striking reversal in the dominant form of tobacco use within 5 years. This finding illustrates how rapidly vaping has supplanted traditional smoking among Navy and Marine Corps personnel, marking a fundamental shift in nicotine consumption with implications for military health monitoring and tobacco cessation programs. Implications The study shows e-cigarette vaping rapidly supplanting traditional cigarette smoking among Navy and Marine Corps personnel. It marks a fundamental shift in nicotine consumption with implications for military health monitoring and tobacco cessation programs. Historically, military personnel have been high-risk for cigarette addiction, yet the uptake of e-cigarettes (vaping) is relatively new. Estimating trends of nicotine-use is important for allocating resources and prioritizing cessation interventions or other programs.